ENTERTAINMENT SHOW IN TELEVISION AS AUTHORIZER’S HEGEMONY TOOL IN “MOCKINGJAY’ NOVEL - Khodijah, Syuri (Program Studi Sastra Inggris, Fakultas Sastra, Universitas Komputer Indonesia Bandung, 2018)
This article analyzes about television as medium to do hegemony which is executed by President Alma Coin, one of authorizers in â€œMockingjayâ€ novel which is the focus of the performer of hegemony in this article. Coin is the authorizer of District 13â€”outcast region of a state named Panem. She wants to overthrow President Coriolanus Snow from his position as the authorizer of Panem. To do her hegemony, Coin ignites uprising movement by using Katniss Everdeen as Mockingjayâ€”face of the uprisingâ€”and make Proposâ€”propaganda spotsâ€”which is broadcasted to all over Panem through television. Katniss is used by Coin as puppet to deliver her government speeches because Katniss has huge influence in Panem. Coin also makes Propos which contains footage videos of Snowâ€™s cruel authorization which will doctrine Panem subjects and lead them into their belief alteration to Coin as a purpose. This article uses qualitative descriptive method to analyze television which is used as medium of authorizerâ€™s hegemony in â€œMockingjayâ€ novel. The result of this article shows that television certainly can be a medium of authorizer, in this case is Coin, to do hegemony. Coin makes Propos and broadcasts it in television which aims to impose her political opponent, Snow, and to earned the whole Panem subjectsâ€™ voice. In addition, Coin also uses Katniss as the main star of her Propos because of the influence that Katniss has.